Fifty years of Data Envelopment Analysis - Mergoni, Anna; Emrouznejad, Ali; De Witte, Kristof (European journal of operational research, 2025)
•A synthesized hands-on literature review of 50 years of Data Envelopment Analysis.•A structured, six-stage framework to streamline DEA analyses.•A practical guide to implement non-parametric efficiency analysis. Data Envelopment Analysis (DEA) has emerged as a powerful analytical tool, revolutionising the field of Operational Research (OR) and contributing to advancements in performance evaluation methodologies. This practical literature review delves into the extensive body of research surrounding DEA, focusing particularly on its evolution within the last 50 years. Drawing upon a comprehensive analysis of publications in top-tier OR journals this literature review paper offers analysis of DEA's development, highlighting key milestones, methodological advancements, and emerging trends. Central to this exploration is the introduction of the COOPER-framework—a structured approach derived from influential papers in the field—that provides a state-of-the-art synthesis of DEA methodologies. Emphasizing non-parametric models and addressing the challenges posed by complex decision-making environments, the COOPER-framework serves as a valuable resource for both experienced scholars and newcomers to the field. By incorporating feedback loops to navigate interconnected decisions, the framework ensures the reliability and robustness of DEA analyses. Through this literature review, we aim to not only refine existing methodologies but also provide a practical tool for researchers, fostering collaboration and driving further innovation in the field of DEA.